Is Delaware losing its cases? - Armour, J; Black, B; Cheffins, B (Wiley, 2012)
Delaware's expert courts are seen as an integral part of the state's success in attracting incorporation by public companies. However, the benefit that Delaware companies derive from this expertise depends on whether corporate lawsuits against Delaware companies are brought before the Delaware courts. We report evidence that these suits are increasingly brought outside Delaware. We investigate changes in where suits are brought using four hand‐collected data sets capturing different types of suits: class action lawsuits filed in (1) large M&A; and (2) leveraged buyout transactions over 1994–2010; (3) derivative suits alleging option backdating; and (4) cases against public company directors that generate one or more publicly available opinions between 1995 and 2009. We find a secular increase in litigation rates for all companies in large M&A; transactions and for Delaware companies in LBO transactions. We also see trends toward (1) suits being filed outside Delaware in both large M&A; and LBO transactions and in cases generating opinions; and (2) suits being filed both in Delaware and elsewhere in large M&A; transactions. Overall, Delaware courts are losing market share in lawsuits, and Delaware companies are gaining lawsuits, often filed elsewhere. We find some evidence that the timing of specific Delaware court decisions that affect plaintiffs' firms coincides with the movement of cases out of Delaware. Our evidence suggests that serious as well as nuisance cases are leaving Delaware. The trends we report potentially present a challenge to Delaware's competitiveness in the market for incorporations.